The response to plant mitogens of two subpopulations of lymphocytes in a case of chronic lymphocytic leukaemia - Smith, J. L. (1973)
The effect of the plant mitogens, phytohaemagglutinin, pokeweed mitogen and concanavalin A, on the peripheral lymphocytes was studied in a case of chronic lymphocytic leukaemia in which the leukaemic cells could be identified by characteristic crystalline IgA inclusions. Compared with normal lymphocytes, the patient's lymphocytes showed reduced and delayed responses during culture for 8 days. Whether assessed by light or electron microscopy or immunofluorescence, cells with inclusions never represented more than a small percentage (approx. 3%) of the transformed cells, or those showing (3)H-thymidine uptake. It was concluded that while a small percentage of the leukaemic cells do transform in response to mitogens, the overall delayed response was due to outgrowth of the normal lymphocyte population.